Trade, infrastructure, and development - Marcelo Olarreaga (Asian Development Bank Institute (ADBI), 2016)
In this paper, the literature on trade and development is surveyed, especially that regarding the role of complementarities associated with trade infrastructure. The empirical literature shows that, on average, trade causes growth, but the relationship is far from homogeneous across countries since initial conditions matter. Although the empirical literature shows that investment in soft and hard infrastructure has an unambiguously positive impact on trade flows, the theoretical literature argues that priority should be given to investments in national rather than international infrastructure in countries with relatively poor national infrastructure. This paper finds that data support this prediction.
Keywords: F10; O19; O47; 330; trade; trade infrastructure; investments; development